Analisis Implementasi Peraturan Daerah Kabupaten Banyuwangi Nomor 45 Tahun 2015 - Hary Priyanto; Nana Noviana (Departemen Ilmu Administrasi FISIP UNHAS, 2018)
The implementation of governance is very important in public policy making for the realization of a good public policy and can meet the needs of the community. In solving the problems of governance, a policy is required, therefore a policy-making process is required. Objective: To illustrate the phenomenon of government policy implementation on prostitution in Banyuwangi District. This research method is a qualitative research using descriptive approach based on Health Policy perspective. Result of research of Banyuwangi no. 45 of 2015 is expected to provide solutions to the problems of HIV / AIDS that occurred in Banyuwangi. The success of the policy implementation is assessed from the Standards and policy objectives; Resource; Communication; Interorganization and inaugural activities; Characteristics of implementing agents; social, economic, and political conditions, as well as the character of the executive.